A Review of Tobacco User and Non-user - Namrata. N. Nangare; Smitesh. S. Nalage (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The tobacco epidemic continues to grow due to the increasingly irregular and inadequate access to health care in the population and particularly affects LMICs. The occurrence and mobility of different elements in oral smokeless tobacco products STPs were determined because the effects on human health must take into account their ability. We used data from the 2009-2010 national adult tobacco survey a national landline and cell phone survey of adults aged 18 years and older to estimate current use of any tobacco, Cigarettes, cigars, cigarillos, or small cigars or chewing tobacco, snuff or dip water pipes. We stratified estimates by gender, age, education, income, sexual orientation, and US state. Perceptions of tobacco are a relatively unexplored issue in disadvantaged populations in India and France.
Keywords: Tobacco; Saliva; Cotinine; Cancer; Liver; Kidney; Nicotine Test